Integrated education and knowledge-building (social theoretical study) - Maath Ahmed Hasan; Abdullah Hamad (مجلة جامعة الأنبار للعلوم الإنسانية, 2022)
The current study aimed to know the reality of blended education in the Iraqi society, in addition to standing on the most prominent obstacles and challenges facing teachers and students in the application of blended education and an attempt to overcome and overcome them. As well as diagnosing the pros and cons of blended education (e-learning - traditional education) on students' acquisition of knowledge building in their academic courses.